Example #1
0
 def __reduce__(self):
     t = defaultdict.__reduce__(self)
     return (t[0], ()) + (self.__dict__, ) + t[3:]
Example #2
0
 def __reduce__(self):
     t = defaultdict.__reduce__(self)
     return (t[0], ()) + t[2:]
Example #3
0
 def __reduce__(self):
     t = defaultdict.__reduce__(self)
     return (t[0], (self.to_dict(), ), t[2], t[3], t[4])
Example #4
0
 def __reduce__(self):
     t = defaultdict.__reduce__(self)
     return (t[0], ()) + (self.__dict__,) + t[3:]
Example #5
0
 def __reduce__(self):
     t = defaultdict.__reduce__(self)
     return (t[0], ()) + t[2:]
Example #6
0
 def __reduce__(self):
     r = defaultdict.__reduce__(self)
     # override __init__ args
     return (r[0], (), r[2], r[3], r[4]) 
Example #7
0
 def __reduce__(self):
     r = defaultdict.__reduce__(self)
     # override __init__ args
     return (r[0], (), r[2], r[3], r[4])
Example #8
0
 def __reduce__(self):
     t = defaultdict.__reduce__(self)
     return (t[0], (self.to_dict(),), t[2], t[3], t[4])